2017
DOI: 10.1177/1055665617726991
|View full text |Cite
|
Sign up to set email alerts
|

Does Unilateral Cleft Lip and Palate Affect the Maxillary Sinus Volume?

Abstract: The MSVs of the UCLP patients showed a statistically significant decrease compared to those of the controls ( P < .001). There was also a significant difference in the MSVs of the cleft and noncleft sides of the UCLP patients ( P < .05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 22 publications
2
38
0
8
Order By: Relevance
“…29 and Demirtas et al . 30 reported that maxillary sinus volume was negatively affected in UCLP compared with the healthy control group. Hypoplasia of the maxillary caused hypoplastic maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…29 and Demirtas et al . 30 reported that maxillary sinus volume was negatively affected in UCLP compared with the healthy control group. Hypoplasia of the maxillary caused hypoplastic maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados pueden estar relacionados con las discrepancias maxilomandibulares causadas por la fisura labiopalatina. Otros estudios nos muestran que existe una alteración en el desarrollo anteroposterior del hueso maxilar debido a la presencia de fisura labiopalatina; esto podría guardar relación con los resultados de este estudio [11][12][13] . Otro estudio de la AIO del CASP con CASA en pacientes no portadores de fisura labiopalatina, realizado en TCHC, describe no encontrar diferencias en la localización y simetría de la anastomosis cuando compararon el lado derecho con su contralateral izquierdo 10 , lo cual no concuerda con los resultados de este estudio, puesto que cuando comparado el lado FLP con su contralateral NF, en 68 (71,5 %) de los casos la localización de AIO fue asimétrica y solo 27 (28,4 %) de los casos fue simétrico.…”
Section: Discussionunclassified
“…(10,3) Accurate measurement of MS volume is important prior to sinus floor augmentation for implant placement and also during sinus surgery. (2) Many studies evaluated maxillary sinuses volume in CLP patients using different imaging modalities, such as conventional radiographs , multi-slice computed tomography and magnetic resonance imaging (11,12,13,14,15,16) evaluation of MS volume by Conventional radiographs are not accurate due to superimposition of other paranasal sinuses and craniofacial bones , magnetic resonance imaging and computed tomography are used for 3D visualization of the sinus anatomy. But it is limited due to high patient radiation dose and high cost with CT, limited access and high cost with MRI.…”
Section: Annals Of Tropical Medicine and Public Healthmentioning
confidence: 99%
“…These results agreed with the results of the present study. In 2017 Demirtas et al (2) using CBCT to compare the MS volume between 44 CLP and 44 control subjects. They reported anon-significant difference between the right and left side of control group , and a significant difference in MS volume between the cleft and Control groups.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation